2018
DOI: 10.4324/9781351106177
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructures in Practice

Abstract: Accepted VersionCass, N., Faulconbridge, J. and Connaughton, J. (2018) The office: how standards define 'normal' design practices and work infrastructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…In line with this, recent studies have considered economics in everyday life and have given explanations for how prices may influence practices in ways other than in an economically rational approach [31][32][33][34]. For instance, Strengers argued that price can convey meanings to consumers, for instance, meanings of scarcity or abundance [34]. In our case, the meaning that is conveyed by the price difference is related to questions of self-sufficiency; using one's produced electricity is given meaning through the difference in price between what prosumers can sell electricity for and what prosumers must pay for the electricity they buy.…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 97%
See 1 more Smart Citation
“…In line with this, recent studies have considered economics in everyday life and have given explanations for how prices may influence practices in ways other than in an economically rational approach [31][32][33][34]. For instance, Strengers argued that price can convey meanings to consumers, for instance, meanings of scarcity or abundance [34]. In our case, the meaning that is conveyed by the price difference is related to questions of self-sufficiency; using one's produced electricity is given meaning through the difference in price between what prosumers can sell electricity for and what prosumers must pay for the electricity they buy.…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 97%
“…Thus, the metering scheme makes a difference; however, the qualitative interviews revealed that this should not be understood in a simple rational economic sense. In line with this, recent studies have considered economics in everyday life and have given explanations for how prices may influence practices in ways other than in an economically rational approach [31][32][33][34]. For instance, Strengers argued that price can convey meanings to consumers, for instance, meanings of scarcity or abundance [34].…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 99%
“…and by their interdependencies with material infrastructures and the ecological world-system (cf. Shove, 2016; Elder-Vass, 2017). Thus, if different trajectories of sustainability are to be analyzed, one has to ask which enabling and constraining socio-material structures suggest which practices to economic, political, and civil-society actors, and which affective/moral imaginaries these practices are associated with.…”
Section: Trajectories Of Sustainability and Their Structures Practices And Imaginariesmentioning
confidence: 99%
“…They enable and subtly order the continuous production of social realities. This specific power of ‘conducting conduct’ ( Foucault, 1982 ) is appreciated by ‘infrastructural inversion’ ( Bowker, 1994 ), by bringing infrastructures back above ground by means of focusing attention on their construction and ordering effects ( Barlösius, 2019 ; Bowker et al, 2009 ; Bueger, 2015 ; Opitz and Tellmann, 2015 ; Shove and Trentmann, 2018 ).…”
Section: Infrastructuring Knowledge Flows: the Politics Of An Emerging Instrument Spacementioning
confidence: 99%